Revealing Student Murder Cases: How Criminology and Criminal Law See this Phenomenon? - Syah, Ary Muktian; Sinambela, Erland Regif Kristian (Law Research Review Quarterly, 2023)
This study delves into the murder case involving DS students from the Indonesian Art Institute (ISI) in Yogyakarta, orchestrated by an individual identified as YF. The victim group, comprising six individuals on two-wheeled vehicles traveling from the west, encountered two to five perpetrators in the Sewers area of Mataram. A dispute ensued when the two groups refused to yield to each other, escalating into a physical altercation. The altercation persisted until the perpetrators formally challenged the victims to a fight, ultimately leading to one victim, specifically YF, being stabbed. The study employs a research method with a normative juridical approach, utilizing a case-oriented methodology. Multiple legal references serve as the foundation for analyzing the subject matter. The focus of this paper centers on the Role of Criminal Law in addressing the murder case involving ISI students in Yogyakarta. Additionally, it explores the position of the murder victims within the framework of Criminal Law, both in terms of Positive Law and through the lens of Victimological Studies. The paper concludes by highlighting the multifaceted functions and objectives of the law. As a nation governed by the rule of law, Indonesia has established a Criminal Code that comprehensively addresses various offenses, with specific provisions dedicated to crimes such as murder.